Brand Experience as a Driver of Consumer Loyalty:The Mediating Roles of Perceived Quality and Brand Trust in Digital Beauty Platforms - Nabilah Syaharani Dewasandra; Mahir Pradana; Arry Widodo (Harmoni Economics: International Journal of Economics and Accounting, 2025)
The high bounce rate of the SOCO by Sociolla app, reaching 57.8%, and the decline in user engagement indicate a serious challenge in maintaining consumer loyalty amidst highly dynamic digital platform competition. In an era when consumers have many alternatives and high expectations for digital experiences, building meaningful relationships through brand experience is crucial. Brand experience encompasses not only functional interactions but also emotional and sensory dimensions that shape consumer perceptions of service value and quality. This study aims to analyze the influence of brand experience on brand loyalty by including perceived quality and brand trust as mediating variables. A quantitative approach was used through the Structural Equation Modeling (SEM) method on 430 active SOCO app users. The results showed that brand experience significantly influences brand loyalty directly (t=2.195, p=0.014) and also indirectly through perceived quality (t=2.457, p=0.007) and brand trust (t=5.563, p=0.000). Overall, this model explains 62.7% of the variance in brand loyalty. These findings underscore the importance of experiential marketing strategies in increasing customer satisfaction, building trust, and maintaining long-term loyalty. A strong brand experience can create deep emotional connections, strengthen perceptions of service quality, and foster brand trust, particularly in the digital beauty sector, which relies heavily on image and user convenience. Theoretically, this study contributes to the development of brand loyalty models in the digital environment. Practically, the results of this study provide guidance for digital beauty app managers like SOCO to design more immersive, personalized, and consistent user experience strategies to increase customer retention and strengthen their competitive position.